Hubungan Kesejahteraan Spiritual Dengan Kesehatan Mental Mahasiswa/I Keperawatan Stikes Suaka Insan - Gertrudis Tutpai; Nita Natalia Bungas; Maria Frani Ayu Andari Dias; Ermeisi Er Unja (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Knowing the relationship between spiritual well-being and mental health in Nursing STIKES Asylum Students in 2022. The type of research used in this study was quantitative using a correlation research design with a cross-sectional research design. The number of samples in this study were 137 respondents to nursing students at STIKES Asylum insan, which were obtained by simple random sampling technique. Data collection was carried out using a questionnaire to measure spiritual well-being using the Spiritual Health And Life-Orientation Measure (SHALOM) and to measure mental health using a self-reporting questionnaire (SRQ). Data analysis was performed by using descriptive and inferential statistical tests. The Spearman rank test on both variables shows that spiritual well-being has no relationship to mental health with a p value (Sig=0.365) > 0.05 (a), with a strength value of r = -0.078. Spiritual well-being has no relationship with mental health status in nursing students.